MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA PENGGELAPAN BENDA JAMINAN FIDUSIA - Supriyadi Supriyadi (Masalah-Masalah Hukum, 2014)
Fiduciary is born based on trust between the fiduciary giver (debtor) and the fiduciary receiver (creditor), in which in the fiduciary agreement, although the fiduciary receiver has provided fund to fiduciary giver, but the bail object is still controlled by fiduciary giver. With object mastered by the fiduciary giver, they often embezzled/transferred the object to a third party. The fraud settlement can be reached through litigation, namely through the regular judicial proceedings, and the need to take another alternative is through penal mediation to reduce the burden or even a buildup of cases in the courts related to embezzlement